Characterization of drum-dried thickeners for dysphagia-adapted liquid diets - Pattra Wattanapan; Sirada Sungsinchai; Siriporn Tanjor; Suphan Yangyuen; Cherdpong Chiawchanwattana; Sakamon Devahastin; Chalida Niamnuy (Applied Food Research)
Dysphagia patients require suitable thickened liquid foods that are easy and safe to swallow. The use of thickeners is one possible approach to increasing the viscosity of liquid foods. This study aimed to develop a powdery thickener with high dispersibility and thickening capability using drum drying. The experimental design for thickener polysaccharides—namely xanthan gum (XG), carboxymethyl cellulose (CMC), and modified corn starch (MCS)—was conducted using the extreme vertices method (10 formulas), followed by mixing with maltodextrin, potassium chloride, and water. The solution was dried using a drum dryer at 120 °C. The dried samples were evaluated in terms of thickening capability, solubility, and stability in thickened liquid foods. The moisture content of the dried samples ranged from 4.40% to 6.06% (d.b.). The use of XG as the main thickener polysaccharide in the prepared thickeners resulted in higher viscosity and stability of all thickened liquid foods compared to CMC and MCS, respectively. In the cases of water, orange juice, milk, and cream soup thickened by the prepared thickener, the formulation containing only XG as the thickener polysaccharide exhibited the highest viscosities. Although orange juice and cream soup thickened with this formulation showed lower viscosities than those thickened with a commercial thickener, the same honey-like consistency was observed. Conversely, water and milk thickened with this formulation demonstrated higher viscosities than those thickened with the commercial product. The results of rheological, tribological, in vitro digestibility, and swallowing tests for this thickener were comparable to the commercial thickener, indicating its potential for use in dysphagia liquid diets.